Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1080/00207594.2011.596541
|View full text |Cite
|
Sign up to set email alerts
|

The making of autobiographical memory: Intersections of culture, narratives and identity

Abstract: Autobiographical memory is a uniquely human form of memory that integrates individual experiences of self with cultural frames for understanding identities and lives. In this review, we present a theoretical and empirical overview of the sociocultural development of autobiographical memory, detailing the emergence of autobiographical memory during the preschool years and the formation of a life narrative during adolescence. More specifically, we present evidence that individual differences in parental reminisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
220
0
25

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 295 publications
(259 citation statements)
references
References 112 publications
3
220
0
25
Order By: Relevance
“…By other definitions, even this larger set of criteria would be considered insufficient to differentiate autobiographical from episodic memory. In the literature on self identity, for example, autobiographical memory is defined as a capacity that permits construction of a sequence of memories of temporally linked events, such as expressed in a life story or autobiography (e.g., Fivush, Habermas, Waters, & Zaman, 2011;Fivush & Zaman, 2014;Habermas & Bluck, 2000;McAdams, 2001; see also Conway & Pleydell-Pearce, 2000;Thomsen, 2009). From this perspective, retrieval of an autobiographical memory involves autobiographical consciousness, defined as a form of consciousness of a present self who is different from-yet temporally linked to-the past self who experienced the event (Fivush, 2012; see also Fivush & Zaman, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By other definitions, even this larger set of criteria would be considered insufficient to differentiate autobiographical from episodic memory. In the literature on self identity, for example, autobiographical memory is defined as a capacity that permits construction of a sequence of memories of temporally linked events, such as expressed in a life story or autobiography (e.g., Fivush, Habermas, Waters, & Zaman, 2011;Fivush & Zaman, 2014;Habermas & Bluck, 2000;McAdams, 2001; see also Conway & Pleydell-Pearce, 2000;Thomsen, 2009). From this perspective, retrieval of an autobiographical memory involves autobiographical consciousness, defined as a form of consciousness of a present self who is different from-yet temporally linked to-the past self who experienced the event (Fivush, 2012; see also Fivush & Zaman, 2014).…”
mentioning
confidence: 99%
“…Thus, developments in verbal and narrative skill herald cognitive benefits of rehearsal and organization, which are advantageous to memory. Beyond individual memories, developments in narrative skills also make possible construction of a life story or autobiography that weaves together the individual experiences of one's life into a sequence of temporally linked events (e.g., Brewer, 1980;Fivush et al, 2011;McAdams, 2001). Narrative evidence of this development becomes apparent only in adolescence (e.g., Bohn & Berntsen, 2008Fivush & Zaman, 2014;Habermas & Bluck, 2000).…”
mentioning
confidence: 99%
“…These studies have found that parental variance in behavior during reminiscing-particularly the extent to which a parent is elaborative-relates to children's vocabulary (Peterson et al 1999), independent narrative skills (Reese et al 2010), autobiographical memory (Fivush et al 2011), and social and emotional skills (Goodvin and Romdall 2013;Haden and Ornstein 2009;Reese and Cleveland 2006). The strength of this evidence has led to the proposal that elaborative forms of reminiscing should constitute the basis of clinical interventions to develop children's language and memory skills (Wareham and Salmon 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that there are cultural differences in reminiscing and elaborative style (Fivush et al 2011;Reese and Neha 2015). In this article, for reasons of space and clarity, we focus solely on research in the Western context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation